STUDI KASUS MALPRAKTEK DOKTER DI RUMAH SAKIT(PERKARA PERDATA NOMOR 57 PK/PDT/2021 DAN PERKARA PERDATA NOMOR 1145 K/PDT/2017) - Siti Rokayah (2022)
Doctors, dentists, patients and hospitals each have the right to obtain legal protection. However, it is undeniable that doctors and dentists in carrying out health services and hospitals in providing medical treatment and health restoration services are often found to be violations, errors or omissions against patients which are generally known as malpractice. Not infrequently when there is an alleged malpractice of a doctor in a hospital, a claim for civil compensation arises from a patient who feels aggrieved by medical services from a doctor/dentist through filing a civil lawsuit to the court. The purpose of this study was to determine the juridical impact of the Decision on Civil Case Number 57 PK/Pdt/2021 juncto Number 42 K/PDT/2018 juncto Number 614/PDT/2016/PT.DKI juncto 625/Pdt.G/2014/PN.JKT.BRT and Decision on Civil Case Number 1145 K/PDT/2017 in conjunction with Number 123/PDT/2016/PT.DKI in conjunction with Number 569/PDT.G/2013/PN.JKT.PST. against malpractice of doctors in hospitals. The type of research used is normative legal research, which uses various sources of primary, secondary and tertiary legal materials that are used as databases. The data obtained are studied and discussed as a comprehensive material that produces qualitative normative data. The results of this study are able to determine the juridical impact of the Decision on Civil Case Number 57 PK/Pdt/2021 juncto Number 42 K/PDT/2018 juncto Number 614/PDT/2016/PT.DKI juncto 625/Pdt.G/2014/PN.JKT. BRT and Civil Case Decision Number 1145 K/PDT/2017 in conjunction with Number 123/PDT/2016/PT.DKI in conjunction with Number 569/PDT.G/2013/PN.JKT.PST. against malpractice of doctors in hospitals and that there is still no standard or standard guideline specifically in the health sector for judges in deciding cases of malpractice of doctors in hospitals. Suggestions in this study require doctors and hospitals to carry out their obligations properly in providing medical services in accordance with professional standards and standard operating procedures as well as the medical needs of patients. Likewise, hospitals can carry out medical treatment and health recovery services in accordance with hospital service standards in order to reduce or at least no longer have malpractice doctors in hospitals so as to avoid claims for compensation from patients and or patients' families. Keywords: malpractice, doctor, hospital